Hot Ion Flows in the Distant Magnetotail: ARTEMIS Observations From Lunar Orbit to ∼−200 RE. Issue 10 (5th October 2017) - Artemyev, A. V.; Angelopoulos, V.; Runov, A.; Vasko, I. Y.
Abstract: Plasma energization in Earth's magnetotail is supported by acceleration processes in (and around) magnetic reconnection regions. Hot plasma flows and strong electromagnetic waves, generated by magnetic energy release during reconnection, transport energy necessary for current system intensification and particle acceleration in the inner magnetosphere. Earth's magnetotail configuration includes two main reconnection regions (X lines): the near‐Earth X line, which has been well studied by several multispacecraft missions, and the distant X line, which has been much less investigated. In this paper, we utilize the unique data set gathered by two ARTEMIS spacecraft in 2010 at radial distances between lunar orbit and ∼200  R E (Earth radii). We identify an X line at around ∼80  R E and collect statistics on hot plasma flows observed around and beyond this distance. Ion spectra within these flows are well fitted by a power law with the exponential tail starting above an energy ϵ 0 ∼ 2–5 keV. Assuming that these spectra are originated at the distant X line, we examine the characteristics of the acceleration at the distant tail reconnection region. Key Points: Collection of hot plasma flows probably originated from distant X line at ∼80  R E Ion spectra within hot flows consist of a power law distribution with the exponential tail starting at energy ∼2–5 keV Observed hot ion spectra can be explained by stationary X line model with the reconnection electric field ∼0.3 mV/m